Solitary pulmonary nodule: medical approach and treatment - Montes-Farah Juan Manuel; Ojeda-Rodríguez Kelman Hanael; Segovia-Fuentes Javier Ignacio; Henao-Castrillón Julio César (Revista Ciencias Biomédicas, 2013)
Introduction: the detection of the solitary pulmonary nodule (SPN) is usually casual.Benign injuries must be differentiated from malignant injuries to establish the adequatemedical monitoring and therapeutic interventions.Objective: to check the current condition of the diagnosis and treatment of SPN.Methods: databases PubMed, Science Direct, OvidSP, EBSCOhost and Scielo werereviewed. The search included systematic reviews, meta-analysis, guidelines, consensusand reviews with keywords got from Mesh: Solitary pulmonary nodule, lung neoplasm,diagnosis and therapy. Publications since 1986 to 2011 were considered.Results: 329 articles were obtained. 55 of them allowed reaching the aim of the review.There are recommendations to study to patients with SPN; the guideline proposed bythe American College of Chest Physician (ACCP) is available. Most of the nodules are ofbenign etiology. The risk of malignancy of SPN is assessed according to risk factors ofthe patient and to the radiological characteristics of the lesion, including: Size, growthrate, calcifications, attenuation, margins, highlight with contrast and metabolic rate.Image studies are: Thoracic radiography, Computed Axial Tomography (CT) of the chestand PET/CT. The SPN with high degree of malignancy must be intervened surgically withminimally invasive technologies as first option. The monitoring of indeterminate andbenign nodules must be done with CT of high resolution and PET/CT if it is indicated.Conclusion: an adequate approach of SPN allows opportune diagnosis of lungneoplasm; it improves the worldwide survival and limits the unnecessary interventions.Rev.Cienc.biomed. 2013;4(1): 125-133.RESUMEN:deben diferenciar las lesiones benignas de las malignas, para establecer el seguimientoy las intervenciones terapéuticas adecuadas.Objetivo: revisar el estado actual del diagnóstico y el tratamiento del NPS.Metodología: se revisaron las bases de datos PubMed, Science Direct, OvidSP,EBSCOhost y Scielo, en búsqueda de revisiones sistemáticas, metaanálisis, guías,consensos y revisiones con palabras claves tomadas del Mesh: solitary pulmonarynodule, lung neoplasm, diagnosis, therapy. Se consideraron publicaciones de 1986 a2011.Resultados: se obtuvieron 329 artículos, de los cuales 55 permitían cumplir el objetivode la revisión. Existen recomendaciones para estudiar a los pacientes que presentanNPS. Está disponible la guía propuesta por American College of Chest Physician (ACCP).La mayoría de los nódulos son de etiología benigna. El riesgo de malignidad del NPS seevalúa según factores de riesgo del paciente y características radiológicas de la lesión,incluyendo: tamaño, tasa de crecimiento, calcificaciones, atenuación, márgenes, realcecon contraste y tasa metabólica. Las ayudas imagenológicas son: radiografía de tórax,TAC de tórax y PET/CT. Los NPS de alto grado de malignidad deben ser intervenidosquirúrgicamente, prefiriendo técnicas mínimamente invasivas. El seguimiento de losnódulos indeterminados y benignos se debe realizar con TAC de alta resolución y PET/CT, si está indicado.Conclusión: un abordaje adecuado del NPS permite diagnósticos oportunos de cáncerde pulmón, mejora la sobrevida global y limita las intervenciones innecesarias. Rev.Cienc.biomed. 2013;4(1): 125-133